2011
DOI: 10.1002/wcs.1156
|View full text |Cite
|
Sign up to set email alerts
|

Self model theory: learning from the future

Abstract: This paper synthesizes findings and theoretical propositions across behavioral, cognitive, and neuropsychological theories, with significant new conceptualizations bearing upon processes of learning and performance. There is a need to explain ultrarapid learning within the framework of cognitive science. In video self modeling and in challenging circumstances, the speed of behavior change appears to be derived from feedforward, in which component behaviors (in the repertoire) are reconfigured to produce a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 76 publications
1
29
0
1
Order By: Relevance
“…The putative human mirror neuron system (Gallese et al, 1996) may have been the mechanism by which the action observation intervention facilitated the ease with which the golfers could generate visual images of themselves performing golf shots. In addition, it is likely that any possible activation of mirror neuron regions in this experiment would have been enhanced through the use of a self-modeling observation intervention, rather than the use of another person as the model (see Dowrick, 2012, for a review).…”
Section: Downloaded By [New York University] At 22:01 14 May 2015mentioning
confidence: 98%
See 1 more Smart Citation
“…The putative human mirror neuron system (Gallese et al, 1996) may have been the mechanism by which the action observation intervention facilitated the ease with which the golfers could generate visual images of themselves performing golf shots. In addition, it is likely that any possible activation of mirror neuron regions in this experiment would have been enhanced through the use of a self-modeling observation intervention, rather than the use of another person as the model (see Dowrick, 2012, for a review).…”
Section: Downloaded By [New York University] At 22:01 14 May 2015mentioning
confidence: 98%
“…Consistent with guidelines for self-modeling interventions (e.g., McCullagh, Law, & Ste-Marie, 2012) only participants' best performances were included in the action observation intervention. This is the most common method of delivering self-modeling interventions in sport settings (Dowrick, 2012). The footage was edited using NCH VideoPad Video Editor Professional 2.11 software to create an individualized action observation DVD.…”
Section: Action Observation Training Programmentioning
confidence: 99%
“…Dowrick () asserts that a rapid behavior change implies dramatic changes in self‐efficacy. Self‐efficacy, the belief that one can complete a task successfully, or meet a specific learning goal, is not always present when students learn new content.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Video modeling can be used with peers, adults, or self as a model (video self-modeling [VSM]). VSM is a specific applica tion of video modeling that allows the child to observe herself or himself, rather than a peer, successfully performing a behavior (Dowrick, 2012). Research on video modeling indicates that watching predominantly positive and/or successful behaviors of oneself, as opposed to negative and/or unsuc cessful behaviors, is an essential ingredient to effective modeling interven tions (Bellini & Akullian, 2007;Dowrick, 2012).…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated that VSM interventions produce substantial intervention, maintenance, and generalization effects across a myriad of dependent variables (Dowrick, 2012). As such, video modeling interventions have recently been identified as "evidence based" for youth with autism spectrum disorders (National Autism Center, 2009).…”
mentioning
confidence: 99%